Social Media Analysis to identify the Main Dimensions of Service Quality for Using BCA Mobile in Indonesia - Aris, Valentino; Alam, Syamsu; Ashdaq, Muhammad; Ruslan, Andi (Entrepreneurship Undergraduate Program at Amkop Business School, 2024)
This research aims to analyze service quality in the banking sector in Indonesia. We will conduct consumer sentiment analysis on the use of the BCA Mobile application which is used to provide online services to consumers by Bank Central Asia (BCA). Data mining will be carried out to obtain consumer review data on the Google Play Store. The target amount of data is a maximum of 1,000 data. The data will then be analyzed to produce word clouds, topic modeling and sentiment analysis to produce dimensions that influence service quality. Analysis was carried out using the Orange Data Mining Application. The analysis results show dimensions that receive positive, negative and neutral sentiment from BCA Mobile users in Indonesia.Keywords: service quality, data mining, word cloud, topic modeling, sentiment analysis.